1996
DOI: 10.1046/j.1365-2141.1996.d01-1841.x
|View full text |Cite
|
Sign up to set email alerts
|

The CDKN2 gene alterations in various types of adult T‐cell leukaemia

Abstract: The CDKN2 gene, encoding the cyclin-dependent kinase-4 inhibitor p16, is a putative tumour-suppressor gene because it is frequently altered in many malignant tumours. We analysed the CDKN2 gene in 44 cases of adult T-cell leukaemia (ATL) by Southern blot analysis, polymerase chain reaction-mediated single-strand conformation polymorphism (PCR-SSCP) analysis, and direct sequencing. Southern blot analysis detected a homozygous deletion of the CDKN2 gene in 5/44 patients (11.4%). Mutational analysis by the PCR-SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…Since p15 Ink4b induces growth arrest associated with differentiation or apoptosis, it is not usually expressed in normal or transformed proliferating hematopoietic cells (Herman et al, 1997;Iravani et al, 1997;Malumbres et al, 1997;Uchida et al, 1997;Malumbres et al, 1999). In the present study, we found that transformed murine monocytic cells with exogenously expressed c-Myc were an exception.…”
Section: Discussionmentioning
confidence: 37%
“…Since p15 Ink4b induces growth arrest associated with differentiation or apoptosis, it is not usually expressed in normal or transformed proliferating hematopoietic cells (Herman et al, 1997;Iravani et al, 1997;Malumbres et al, 1997;Uchida et al, 1997;Malumbres et al, 1999). In the present study, we found that transformed murine monocytic cells with exogenously expressed c-Myc were an exception.…”
Section: Discussionmentioning
confidence: 37%
“…This region is deleted in a wide variety of other human tumors including squamous cell carcinoma of the bladder (GonzalezZulueta et al, 1995;Cairns et al, 1995a), non small cell lung carcinoma (de Vos et al, 1995), B cell lymphoma (Uchida et al, 1995) pancreatic cancer (Caldas et al, 1994), glioma , esophegeal carcinoma (Liu et al, 1995) and melanoma (Kamb et al, 1994b). Frequent loss at 9p21 ± 22 occurs as an early event in head and neck cancer progression and was found in both invasive and preinvasive lesions (Van de Riet et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…92,[139][140][141][142][143][144][145] Several investigators including ourselves have reported alterations of the p16 occurring in 17-68% of the acute and 5-26% of the chronic ATLL samples and the p15 gene was structurally abnormal in 21-30% of the acute and 0-13% of the chronic ATLL specimens. 90,[146][147][148][149][150] In total, genomic alterations of the p16 gene occurred in 55 of 136 acute/ lymphomatous (40%) cases and nine of 79 (11%) chronic/smoldering ATLL samples. For the p15 gene, 30 of 111 (27%) acute/lymphomatous cases and three of 60 (5%) chronic/smoldering ATLL samples had alterations.…”
Section: Role Of Ink4 Family In Atllmentioning
confidence: 99%